ナンキョク ヒョウショウ ニオケル ケッショウ リュウ セイチョウ ダイ1カイ ナンキョク キスイケン シンポジウム - 成田, 英器; ナリタ, ヒデキ; 前野, 紀一; マエノ, ノリカズ; NARITA, Hideki; MAENO, Norikazu (国立極地研究所, 1979)
P(論文) 南極みすほ基地て掘削回収した雪試料を用い,その試料の薄片から結晶粒の平均断面積を測定し,深さ50mまての結晶粒の成長過程を調べた.結晶粒の平均断面積は時間に比例して増加した.しかし,結晶粒の成長曲線は深さ約35mて不連続となった.成長曲線のこう配から求められる結晶粒の成長速度は深さ35mより浅い所の値より35m以深の値の方が2倍も大きかった.この違いは,積雪の荷重による応力増加のためか,35m以深の雪の層て雪の年間蓄積量を過少評価したためと考えられる.35m以浅て得られた結晶粒成長速度をほかの観測結果と比較することにより,みずほ基地の年間蓄積量は約70kg m^<-2>a^<-1>と見積られた.結晶粒の成長曲線が深さ約35mて不連続になること,およびその層て成長速度が急に増加することから,この雪が蓄積した頃,雪の蓄積量の少ない寒冷な時期が襲来したことが示唆された.結晶粒成長曲線から,寒冷期は約340年前に約70年間続いたと推定される. Measurements of the mean cross-sectional area of crystal grams in snow were made with core samples drilled at Mizuho Station, Antarctica. It was found that the cross-sectional area of crystal grains in snow increased with increasing depth till the depth of about 50 m. The relationship between the cross-sectional area of crystal grains and the time elapsed was essentially linear, but the growth rate of crystal grams was larger in snow at depths below 35 m. The increase in the growth rate can be attributed to the stress-enhancement or the smaller rate of snow accumulation From the growth rate of crystal grains in snow above 35 m, the net accumulation rate at Mizuho Station was estimated to be roughly 70 kg m^<-2>a^<-1> 0n the basis of the discontinuity of growth curves and the apparent increase in the growth rate of crystal grains, a colder climate or period of smaller snow accumulation was suggested to have lasted for about 70 years roughly 340 years ago. departmental bulletin paper